A Review: Antimicrobial Therapy for Human Pythiosis - Sadeep Medhasi; Ariya Chindamporn; Navaporn Worasilchai (MDPI AG, 2022)
Human pythiosis is associated with poor prognosis with significant mortality caused by Pythium insidiosum. Antimicrobials' in vitro and in vivo results against P. insidiosum are inconsistent. Although antimicrobials are clinically useful, they are not likely to achieve therapeutic success alone without surgery and immunotherapy. New therapeutic options are therefore needed. This non-exhaustive review discusses the rationale antimicrobial therapy, minimum inhibitory concentrations, and efficacy of antibacterial and antifungal agents against P. insidiosum. This review further provides insight into the immunomodulating effects of antimicrobials that can enhance the immune response to infections. Current data support using antimicrobial combination therapy for the pharmacotherapeutic management of human pythiosis. Also, the success or failure of antimicrobial treatment in human pythiosis might depend on the immunomodulatory effects of drugs. The repurposing of existing drugs is a safe strategy for anti-P. insidiosum drug discovery. To improve patient outcomes in pythiosis, we suggest further research and a deeper understanding of P. insidiosum virulence factors, host immune response, and host immune system modification by antimicrobials.